2018
DOI: 10.1038/s41598-018-21558-9
|View full text |Cite
|
Sign up to set email alerts
|

Intratesticular injection followed by electroporation allows gene transfer in caprine spermatogenic cells

Abstract: The production of transgenic livestock is constrained due to the limited success of currently available methods for transgenesis. Testis mediated gene transfer (TMGT) is an emerging method that shows a high success rate in generating transgenic mice. In this study, we report a newly developed protocol for electroporation-aided TMGT to produce a transgenic goat. The injectable volume and concentration of the transgene were first standardized, and then electroporation conditions were optimized in vitro. In vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…After a specific interval, injected males can then be used to naturally mate with females to produce transgenic founders. TMGT was initially applied in sheep and goats to produce transgenic founders with inserted genes including lipoprotein lipase (LPL) (Qin et al, 2012), solute carrier family 7 member 11 (SLC7A11) (He et al, 2012), peroxisome proliferator–activated receptor gamma (PPARγ) (Qin et al, 2013), myogenin (MyoG) (Zhang et al, 2014c), and enhanced green fluorescent protein (eGFP) (Raina et al, 2015; Pramod and Mitra, 2018). In general, despite the potential possibilities of sperm-based strategies to mediate transgenesis, these strategies still require optimization.…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…After a specific interval, injected males can then be used to naturally mate with females to produce transgenic founders. TMGT was initially applied in sheep and goats to produce transgenic founders with inserted genes including lipoprotein lipase (LPL) (Qin et al, 2012), solute carrier family 7 member 11 (SLC7A11) (He et al, 2012), peroxisome proliferator–activated receptor gamma (PPARγ) (Qin et al, 2013), myogenin (MyoG) (Zhang et al, 2014c), and enhanced green fluorescent protein (eGFP) (Raina et al, 2015; Pramod and Mitra, 2018). In general, despite the potential possibilities of sperm-based strategies to mediate transgenesis, these strategies still require optimization.…”
Section: Overview Of Genetic Modification and Relevant Biotechnologicmentioning
confidence: 99%
“…On the other hand, the pIRES2-EGFP after the expression produces into the cell a green-fluorescent protein which stains the transfected cells [28]; the transfection efficiency was evaluated by using the fluorescence microscope Carl Zeiss Axio Vert.A1.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…Figure 8(a) shows a micrograph of the cells incubated with the AuNP-PEG-pIRES2-EGFP nanoparticles. The transfection study demonstrated that the AuNP-PEG enter into the cells with the pDNA and it allows the expression of the plasmid which stains the cell due to the transcription of the green fluorescent protein [28].…”
Section: Cellular Transfection and Cytotoxicitymentioning
confidence: 99%
“…Electroporation has been employed to transfer genes into various stages of mammalian embryo development, including sperm cells, embryonic stem cells, and preimplantation embryos and post‐implanted fetuses (Chu et al., 1987; Gagne et al., 1991; Osumi & Inoue, 2001; Wall et al., 1992). Pramod and Mitra (2018) reported successful generation of Tg goats by intratesticular injection of a transgene construct (pIRES2‐EGFP) followed by in vivo electroporation of the entire testis. Immunohistochemistry, quantitative real‐time PCR, and western blotting analyses confirmed the expression of GFP in the seminiferous tubules, testicular cells, and subsequent offspring (Pramod & Mitra, 2018).…”
Section: Resultsmentioning
confidence: 99%